(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Vatakantaka is a very common complaint now days with mild to severe pain in the Pada (foot), Parshini (heel), Gulfa (ankle), Jangha (calf) of the patient. Contemporary medicine describes this condition as Plantar fasciitis which presents as pain in the plantar aspect of the foot frequently associated with heel and ankle pain. It usually does not respond to standard pain management medications, techniques and is a major cause of embarrassment and disability for the patient. This case report refers to the complete remission of Vatakantaka (plantar fasciitis) in a 49 year old female patient with the use of Siravedha (venesection/bloodletting) of the Sira (vein) located 2 Angul (finger width) above Padagata Kshipra Marma (vital point in foot). A total of 3 sittings of Siravedha were done with a gap of 9 days between consecutive sittings. The 1st sitting itself relieved the pain significantly with complete relief from pain and tenderness after all the three sittings were completed. The 3 month long follow up revealed that the symptoms did not reoccur. This case report serves as an example that classical Ayurvedic methods for pain relief such as Siravedha can be explored for improving the management protocols for diseases like Vatakantaka (plantar fasciitis). Further large sample studies are needed to confirm the findings.